2016
DOI: 10.1021/acs.jpcc.6b08931
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of Zeolite Detemplation by Positron Annihilation Lifetime Spectroscopy

Abstract: Templating approaches play a key role in expanding the structural diversity of many important classes of porous materials. Understanding the interaction of the templating agent with the resulting porous framework and the mechanism of detemplation is critical to ensure their effective application. This study explores the scope of positron annihilation lifetime spectroscopy (PALS) to gain insight into the location of tetrapropylammonium (TPA+) industrially employed as a structure directing agent (SDA) in the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Positron annihilation lifetime spectroscopy (PALS) recently developed, was used for quantitative evaluation of mesopore connectivity [ 101 , 102 ]. The positron is the anti-particle of the electron, and when a targeted material is bombarded by positron beam, most of the positrons are directly annihilated and form gamma rays.…”
Section: Rational Design Of Hierarchy At Zeolitic Level: Functional Vs Auxiliary Mesoporesmentioning
confidence: 99%
“…Positron annihilation lifetime spectroscopy (PALS) recently developed, was used for quantitative evaluation of mesopore connectivity [ 101 , 102 ]. The positron is the anti-particle of the electron, and when a targeted material is bombarded by positron beam, most of the positrons are directly annihilated and form gamma rays.…”
Section: Rational Design Of Hierarchy At Zeolitic Level: Functional Vs Auxiliary Mesoporesmentioning
confidence: 99%
“…PALS has emerged as an effective nondestructive technology in probing the porosity of hierarchical zeolites. [ 119,126 ] Ortho ‐positronium ( o ‐Ps) formed by the implanted positron has a long enough lifetime to diffuse through the porous media, but loses energy rapidly as colliding with the channel surface, thus decays with a lifetime proportional to the aperture. As such, PALS provides an indirect yet effective way to evaluate the degree of interconnectivity of mesopore networks in zeolite crystals.…”
Section: Characterization Of Titanium and Hierarchical Structuresmentioning
confidence: 99%
“…Yet, despite having been studied by numerous techniques, the development of the micropore network upon template removal had not been spatially resolved. Using a combination of beam‐PALS measurements, modelling, and simulations coupled to the study of a series of partially detemplated zeolites derived from a single well‐crystallized MFI zeolite sample showed that the detemplation mechanism was best described by an isotropic model favoring the formation of small, isolated template free volumes (Figure b) . Using bulk PALS, a later study identified that the presence of aluminum in the sample could influence the detemplation mechanism .…”
Section: Applications Of Pasmentioning
confidence: 99%
“…This is consistent with the need for improved models to predict o Ps behavior identified in Section . In another study, PALS was applied to derive insights into the detemplation mechanism of MFI‐type zeolites . Templating strategies continue to play an important role in zeolite synthesis due to the structural flexibility they afford.…”
Section: Applications Of Pasmentioning
confidence: 99%